Combination of Paris and Vienna Classifications may Optimize Follow-Up of Gastric Epithelial Neoplasia Patients - Hu, Wen (Med Sci Monit, 2015)
BACKGROUND: The aim of this study was to evaluate the efficiency of the combination of Paris and Vienna classifications in a follow-up study of gastric epithelial neoplasia (GEN) patients. MATERIAL/METHODS: This study was conducted between January 2003 and September 2010, during which 170 biopsy-proven GEN patients were followed up by gastroenterologists and pathologists according to our follow-up regimen (modified Vienna classification). RESULTS: In total, 161 patients with low-grade neoplasia (LGN) and 9 patients with high-grade neoplasia (HGN) were randomly enrolled in our study. Eighteen patients with depressed appearance were observed, of which 9 patients had HGN and 9 patients had low-grade dysplasia (LGD). Three patients with type 0-IIa were observed with low-grade adenoma (LGA), and type 0–I was observed in 2 patients with LGN. Endoscopic or surgical treatments were performed to avoid potential malignancy or bleeding. Two patients with ulcer lesions, 2 patients with non-depressed type 0 appearance, and 3 patients without visible lesions were shown to have higher-grade lesions during follow-up. The misdiagnosis rate of forceps biopsy – 62.07% – was determined by comparing pre- and post-resection diagnoses of 29 patients. CONCLUSIONS: The combination of the Paris and Vienna classifications for GEN may optimize the follow-up routines for patients with suspicious precancerous lesions and may significantly improve the detection of early gastric cancer (EGC) while helping gastroenterologists select the best therapy option.